DOI: 10.1007/978-1-4020-8843-8_20
|View full text |Cite
|
Sign up to set email alerts
|

Antimitotic Drugs For Microprotoplast-Mediated Chromosome Transfer In Plant Genomics, Cell Engineering And Breeding

Abstract: Achievements of the microprotoplast-mediated chromosome transfer (MMCT) technique are summarized. Overcoming technical barriers for large-scale gene transfer through fusion of isolated microprotoplasts, containing one or a few chromosomes, with recipient protoplasts are consi-(amiprophos-methyl and cremart), dinitroanilines (oryzalin) and propyzamideand disrupters of microtubule organizing centers (griseofulvin and phenylcarbamates) for the production of microprotoplasts is analysed. The combined disrupter, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
(93 reference statements)
0
5
0
1
Order By: Relevance
“…Polygenic traits or traits with unknown biochemical or molecular mechanisms (e.g., resistance to certain diseases or stresses and other economically important traits) are still recalcitrant to transfer using methods of genetic engineering. Recently, an alternative asymmetric somatic hybridization method using microprotoplasts (microprotoplast fusion) has been developed [18]. Since microprotoplasts contain only one or a few intact chromosomes, a limited number of chromosomes can be transferred via microprotoplast fusion, resulting in the production of chromosome addition lines with even a single and specific intact chromosome between sexually incompatible species [18,38].…”
Section: Micronucleationmentioning
confidence: 99%
See 2 more Smart Citations
“…Polygenic traits or traits with unknown biochemical or molecular mechanisms (e.g., resistance to certain diseases or stresses and other economically important traits) are still recalcitrant to transfer using methods of genetic engineering. Recently, an alternative asymmetric somatic hybridization method using microprotoplasts (microprotoplast fusion) has been developed [18]. Since microprotoplasts contain only one or a few intact chromosomes, a limited number of chromosomes can be transferred via microprotoplast fusion, resulting in the production of chromosome addition lines with even a single and specific intact chromosome between sexually incompatible species [18,38].…”
Section: Micronucleationmentioning
confidence: 99%
“…Recently, an alternative asymmetric somatic hybridization method using microprotoplasts (microprotoplast fusion) has been developed [18]. Since microprotoplasts contain only one or a few intact chromosomes, a limited number of chromosomes can be transferred via microprotoplast fusion, resulting in the production of chromosome addition lines with even a single and specific intact chromosome between sexually incompatible species [18,38]. In order to apply this technique for improvement of monocot plant species, we established an efficient system for mass-preparation of microprotoplasts of E. coracana.…”
Section: Micronucleationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several techniques can be used for genome fragmentation, such as Uv irradiation (Hall et al 1992) or microprotoplasts (MPPs) (Yemets and Blume 2009). Genome fragmentation of the donor partner stimulates the elimination of much of its redundant genetic material in the somatic hybrid.…”
Section: Advances In Protoplast Fusion and Fragmentationmentioning
confidence: 99%
“…Later it was found that dinitroanilines (oryzalin, trifluralin, chloralin, pendimethalin) and phosphorothioamidates (aminprophos-methyl) destabilize MT and have overlapping sites in plant tubulin. It was proved that dinitroanilines and phosphorothioamidates bind plant α-tubulin with high affinity, inhibit tubulin assembly and disrupt MTs [18,19]. Affected cells do not form a cell plate and may contain restitution and polyploidy nuclei [16].…”
mentioning
confidence: 99%